Risiko Likuiditas dan Risiko Suku Bunga pada Perusahaan Jasa Konstruksi di Lamongan - Fauzi, Muhammad Hamdan Bahrul; Poernomo, Yosef Cahyo Setianto (Universitas Batanghari Jambi, 2024)
In the current era of modern technology and globalization, companies face intense competition both at home and abroad. Failure to carry out performance evaluations is caused by focusing too much on evaluation alone and ignoring other goals such as developing individual skills and abilities in carrying out tasks and company strategies. The purpose of this research is to find out whether liquidity risk affects the performance of construction service companies in Lamongan, whether interest rate risk affects the performance of construction service companies in Lamongan and whether liquidity risk and interest rates affect the performance of construction service companies in Lamongan. The method in this research is a direct survey to the company to request financial report data. The results of this study are that liquidity risk has no significant effect on company performance because the significant value is greater than 0.05 (0.966 > 0.05), interest rate risk does not have a significant effect on company performance because the significant value is greater than 0. 05 (0.316 > 0.05) and liquidity risk and interest rate risk have no effect on the performance of construction service companies because the significant value is greater than 0.05 (0.446 > 0.05).